Efficacy of proton pump inhibitors and H2 blocker in the treatment of symptomatic gastroesophageal reflux disease in infants - Hamid Reza Azizollahi; Mandana Rafeey (Korean Journal of Pediatrics, 2016)
PurposeGastroesophageal reflux disease (GERD) occurs in pediatric patients when reflux of gastric contents presents with troublesome symptoms. The present study compared the effects of omeprazole and ranitidine for the treatment of symptomatic GERD in infants of 2-12 months.MethodsThis study was a clinical randomized double-blind trial and parallel-group comparison of omeprazole and ranitidine performed at Children Training Hospital in Tabriz, Iran. Patients received a standard treatment for 2 weeks. After 2 weeks, the patients with persistent symptoms were enrolled in this randomized study.ResultsWe enrolled 76 patients in the present study and excluded 16 patients. Thirty patients each were included in group A (ranitidine) and in group B (omeprazole). GERD symptom score for groups A and B was 47.17±5.62 and 51.93±5.42, respectively, with a P value of 0.54, before the treatment and 2.47±0.58 and 2.43±1.15, respectively, after the treatment (P=0.98). No statistically significant differences were found between ranitidine and omeprazole in their efficacy for the treatment of GERD.ConclusionThe safety and efficacy of ranitidine and omeprazole have been demonstrated in infants. Both groups of infants showed a statistically significant decrease in the score of clinical variables after the treatment.